Anomalies and Clinical Significance of Mylohyoid Nerve: A Review - Kini S; Somayaji K; Acharya S; Sampath S (Dove Medical Press, 2020)
Sandya Kini,1 Krishnaraj Somayaji,1 Shashirashmi Acharya,1 Shivakumar Sampath2 1Department of Conservative Dentistry and Endodontics, Manipal College of Dental Sciences, Manipal, Manipal Academy of Higher Education, Manipal, India; 2Department of Conservative Dentistry and Endodontics, Vivekananda Dental College for Women, Tiruchengod, Tamilnadu, IndiaCorrespondence: Krishnaraj SomayajiManipal College of Dental Sciences, Manipal, Manipal Academy of Higher Education, Manipal, IndiaTel +918277025409Email sksomayaji@gmail.comBackground: The mylohyoid nerve is a branch of the inferior alveolar nerve (IAN), which is a branch of the posterior division of the mandibular nerve (MN). It is the source of motor nerve supply to the mylohyoid and anterior belly of the digastric muscle. At times, it provides sensory innervation to the mandibular teeth and skin below the chin. Since the location, anatomical variation and communications of the mylohyoid nerve are varied, it becomes clinically important to have an in-depth knowledge when treating patients for dental and maxillofacial procedures. Such anatomical variations of the mylohyoid nerve innervations may account for failure of the nerve blocks and hence, knowledge is very important for the practitioner.Materials and Methods: A thorough literature search was done using the key words mandibular nerve, communications of the mylohyoid nerve, inferior alveolar nerve, lingual nerve, failure of dental anaesthesia, mylohyoid nerve and dental implants “from the Databases – PubMed, Scopus Embase and Web of Science (years 1952– 2020)”.Results: The mylohyoid nerve may contain motor and sensory fibres, it may pass through the mylohyoid groove or canal and communicate with other nerves, which is clinically significant. Such anatomical variations may be one of the reasons for the failure of the inferior alveolar nerve block.Conclusion: Awareness of these variations is very significant in planning treatment and avoiding any unnecessary steps. The most frequently encountered anatomic variation of the mylohyoid nerve was innervation of the submental skin and the anterior teeth.Keywords: mylohyoid nerve, inferior alveolar nerve, mylohyoid groove, anaesthesia